Somaesthetics and Sport - Mugnaini, Giovanni (Scenari, 2023)
This article deals with Somaesthetics, in general, as a branch of contemporary aesthetics, and with its application to Sport related topics, in particular. These topics have been recently investigated as in the book “Somaesthetics and Sport” (2022), edited by Andrew Edgar. In the first section of my article I sketch a brief history of the Philosophy of Sport. The second section is dedicated to a brief overview of Somaesthtetics as a discipline and a preliminary evaluation of its possible applications to Sport issues. The third section (articulated, in turn, in various subsections) is dedicated to a detailed review of the various essays included in the book “Somaesthetics and Sport”. My aim is to highlight the intimate variety of topics that Somaesthetics as a platform can welcome and its disciplinary versatility. The last subsection provides an overall assesment of the books’ aims and their realization, bearing in mind the exploratory nature of the book itself.